Osseointegrated Implants: Strategies for Optimizing the Soft Tissue Seal around Osseointegrated Implants (Adv. Healthcare Mater. 20/2017). Issue 20 (25th October 2017) - Abdallah, Mohamed‐Nur; Badran, Zahi; Ciobanu, Ovidiu; Hamdan, Nader; Tamimi, Faleh
Abstract : Establishing a strong soft tissue seal around bone‐anchored implants, such as orthopedic and dental implants, is critical for preventing bacterial infections and enhancing their long‐term success. The recent findings and challenges concerning the establishment of such a strong soft tissue attachment are reviewed by Mohamed‐Nur Abdallah, Zahi Badran, Ovidiu Ciobanu, Nader Hamdan, and Faleh Tamimi in article number1700549 .